2018
DOI: 10.1016/j.rmed.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The revised GOLD 2017 COPD categorization in relation to comorbidities

Abstract: These findings suggest that the recently modified GOLD categorization is clinically relevant beyond being purely an assessment of symptoms and exacerbations. As the A-D groups correlated with the risk of important comorbidities, with some differences in terms of the correlation with symptoms and exacerbations, the findings underline the importance of identifying comorbidities in COPD, particularly in non-responders to therapy who have high symptoms and/or exacerbation rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 37 publications
3
28
3
1
Order By: Relevance
“…We have included 835 cases with stabile phase of chronic obstructive pulmonary disease, evaluated by spirometry and electrocardiography. Some authors have reported higher age in men as a significant risk factor associated with FEV1 declinement with age, so that the advanced disease stage tends to reduce the FEV1/FVC ratio [11,12]. In our study, both sex were similar age with more female participants, which is contrary to fact that men more frequently suffered from COPD [11,12,13].…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…We have included 835 cases with stabile phase of chronic obstructive pulmonary disease, evaluated by spirometry and electrocardiography. Some authors have reported higher age in men as a significant risk factor associated with FEV1 declinement with age, so that the advanced disease stage tends to reduce the FEV1/FVC ratio [11,12]. In our study, both sex were similar age with more female participants, which is contrary to fact that men more frequently suffered from COPD [11,12,13].…”
Section: Resultscontrasting
confidence: 71%
“…Abnormalities in conduction usually occur late in COPD patients, after the right ventricle hypertrophy has developed to such an extent so that its electrical forces overcome those of the left [11]. In our study, we have found no arrhythmias, despite the fact that almost half of the investigated groups had developed the chronic obstructive pulmonary disease terminal stadium.…”
Section: Resultscontrasting
confidence: 45%
“…Persons with COPD have an average of 7 co-morbidities compared to 3 for other persons (4). The existence of comorbidities is strongly related to COPD exacerbations and symptoms (5). The Body Mass Index, Airflow Obstruction, Dyspnea and Exercise Capacity (BODE) Index is a simple index predicting the risk of death in patients with COPD (6).…”
mentioning
confidence: 99%
“…Kahnert et al 13 analyzed data from 2,228 patients using GODL 2017, and showed that when groups A–D were dichotomized as AC vs. BD (symptoms) and AB vs. CD (exacerbations), all comorbidities had correlation with symptoms and/or exacerbations. In the Danish nationwide cohort study with 22,621 patients, Gedebjerg et al 14 observed that all-cause, respiratory and cardiovascular disease-related mortality were higher for in group B than for patients in group C according to GOLD 2017 classification.…”
mentioning
confidence: 99%